O Lúdico e o imaginário na formação do leitor literário: uma proposta por meio de "A Bolsa Amarela” de Lygia Bojunga - FLÁVIA MARTINS MALAQUIAS (2024)
This study analyzes theoretical and methodological aspects that highlight the importance of playfulness and imagination in the education of elementary school students, promoting critical reading skills and encouraging the pleasure of reading. The research is based on theories from various authors, including "Literature: The Formation of the Reader: Methodological Alternatives" (1988) and "Brazilian Children's Literature: History & Stories" (2009), as well as Reception Aesthetics and the Aesthetic Effect Theory. Gilbert Durand, Gaston Bachelard, and Carl Jung, along with Lev Vygotsky, contribute their perspectives. This theoretical framework guides the approach to teaching literature and the formation of the literary reader, emphasizing playfulness and imagination. The study explores the relevance of these concepts in presenting the literary corpus "The Yellow Bag" by Lygia Bojunga (1976) through a bibliographic review of literary criticism. It investigates how this approach can engage students, stimulating their reflections and contributing to the development of critical reading skills and promoting the pleasure of reading. Additionally, it analyzes how the 2017 National Common Curricular Base (BNCC) addresses the teaching of literature in elementary school, verifying the application of its principles and guidelines in pedagogical practice for the formation of literary readers. The research concludes by highlighting the importance of playfulness and children's imagination as essential tools in education and culture, playing a significant role in forming literary readers and enriching the aesthetic appreciation of the literary text. The BNCC establishes that the teaching of literature should promote the development of reading and text interpretation skills, as well as encourage the formation of critical and creative readers, emphasizing the importance of contact with diverse literary works. Playfulness and imagination are recognized as essential elements to engage students and stimulate the pleasure of reading, favoring the development of cognitive and socio-emotional skills. The reception teaching method has proven to be an effective methodology for this process of forming literary readers.